Frequency of Subclinical Hypothyroidism among Patients of Polycysitic Ovarian Syndrome (PCOS) - Abdullah Choudhry, Mehrunisa, Muhammad Faiq Umar, Saima Saif, Quratulain Haider, Murtaza Jaffar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Polycystic ovarian syndrome (PCOS) is the most common form of chronic anovulation associated with androgen excess; perhaps occurring in 5-10% of reproductive women. PCOS is viewed as a heterogeneous disorder of multifactorial etiology. It is also associated with increased metabolic and cardiovascular risk factors. Subclinical hypothyroidism is “mild” thyroid failure in which thyroid stimulating hormone (TSH) is elevated and free thyroxine (fT4) is normal. Objective: To determine the frequency of subclinical hypothyroidism among patients of polycystic ovarian disease presenting in the outpatient department of tertiary care hospital. Study Setting: The Study was conducted in Mayo Hospital, Lahore. Duration of Study: June 5, 2019 to January 3, 2020 Study Design: Cross-Sectional Study Methods: All polycystic ovarian disease patients were enrolled. Blood samples of the patients were taken by using aseptic techniques and sent to pathology laboratory for measurement of serum TSH level. The frequency of subclinical hypothyroidism among patients of polycystic ovarian disease was identified. Data were entered and analyzed using SPSS v25.0. Data were stratified for age and BMI to deal with effect modifiers. For post stratification, Chi-square test was applied to see the significance. A p-value≤0.05 was considered significant. Results: Total 136 patients with polycystic ovarian disease were selected for this study. Mean age was 28.4±7.9 years. Among 136 patients, 26(19.1%) had subclinical hypothyroidism. By stratification of subclinical hypothyroidism, it was found that age >30 years and obese had significant effect having subclinical hypothyroidism (p=0.00001, p=0.001). Conclusion: Subclinical hypothyroidism may be a modifiable risk factor, associated with polycystic ovarian disease. Steps should be taken to minimize more this risk factor by screening and early intervention.